Root and Canal Anatomy of Maxillary and Mandibular Teeth in Imperial Rome - Çelik, Nezif; Eskibağlar, Mehmet; Demir, Müslüm (Harran University, 2024)
Abstract Objectives:In recent years, root and canal anatomy has been studied in detail by endodontists to ensure successful endodontic treatment. This study aims to investigate the root and canal morphology of the Late Roman populations living 1800 years ago.Method: Eighty-one nine mandibular and six maxillary teeth were scanned using X Radius Trio 3D Cone beam computed tomography CBCT (Castellini, Bologna, Italy) at 90 kVp, 13–16 mA, 13x16, 13x10 FOV, 0.03 mm voxel size. Multiplanar reconstruction images were obtained using iRYS (Castellini) software. Eighty-one mandibular and six maxillary teeth were scanned using CBCT. Result: After this scan, one premolar tooth among 39 teeth in the maxilla was identified as Vertucci Class ?. In the mandibular, all of the canines were single rooted; one of them was identified as Vertucci Class ?. Of the first molars, all were two-rooted; two of them were identified as Vertucci Class ? and one of them as Vertucci Class ?. All of the ten mandibular second molars examined were two-rooted, and no type C canal configuration was found. Conclusion: The root canal anatomy of the 81 scanned teeth showed considerable similarity to the root canal morphology of today’s societies. Keywords: Roman, Mandibular, Maxillary, Morphology, Canal.
Keywords: Endodontics; Endodonti